2022
DOI: 10.1101/2022.06.24.497458
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural inventory of cotranslational protein folding by the eukaryotic RAC complex

Abstract: Folding of nascent chains emerging from the ribosome is a challenge in cellular protein homeostasis, which in eukaryotes is met by an Hsp70 chaperone triad directly binding at the ribosomal tunnel exit. The conserved ribosome-associated complex (RAC) consists of the non-canonical Hsp70 Ssz1 and the J-domain protein Zuotin (Zuo1), which in fungi acts together with the canonical Hsp70 protein Ssb. Here, we determined high-resolution cryo-electron microscopy structures of RAC bound to the 80S ribosome. RAC adopts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Other published structures of RAFs in context of the ribosome, such as NAC 4 , RAC 5,6 and SRP 2,3 show a similar scenario, where a concurrent binding would not be possible, unless adaptive structural rearrangements occur at the PTE (Fig. 5).…”
Section: The Insert Domain Enables Adaptive Binding To Ribosomementioning
confidence: 84%
See 1 more Smart Citation
“…Other published structures of RAFs in context of the ribosome, such as NAC 4 , RAC 5,6 and SRP 2,3 show a similar scenario, where a concurrent binding would not be possible, unless adaptive structural rearrangements occur at the PTE (Fig. 5).…”
Section: The Insert Domain Enables Adaptive Binding To Ribosomementioning
confidence: 84%
“…The signal recognition particle (SRP) has been among the first RAFs studied in detail in context of the ribosome 2,3 , and recently in combination with the nascent polypeptide associated complex (NAC), which revealed their interplay at the peptide tunnel exit (PTE) 4 . Structures of the ribosome associated complex (RAC) 5,6 provided insights into chaperone binding and dynamics at the 80S ribosome. However, our understanding of enzyme function at the eukaryotic ribosome is lagging behind, as only information on the N-terminal Acetyltransferase A (NatA) complex from S. cerevisiae is available to date 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The sole exception is the absence of the CTH from the MPT map 10 , where it would clash with the gate latch helices of the PAT complex (Figure 4A). It would also clash with SRP (via SRP54’s M-domain) 53,77,78 , NAC (via its ribosome-binding helices) 67 , RAC (via Zuo1) 79 , NatA (via Nat1) 80 (Knorr et al 2019), and NatB (via MDM20) 81 .…”
Section: Resultsmentioning
confidence: 99%
“…TF is also the only known chaperone in prokaryotes that binds ribosomes even though other ATPase chaperones, including Hsp70, can associate with nascent chains 34 . By contrast, studies of co-translational protein folding in eukaryotes have shown that RAC exerts control over the Hsp70 ATPase cycle by a complex and still poorly understood mechanism 5,6,10,35 . In addition, eukaryotic ribosomes are bound to stoichiometric amounts of NAC 3 .…”
Section: Ypl225w Is a Gtp-dependent Eef1a Foldasementioning
confidence: 93%
“…How does the eukaryotic ribosome choreograph co-translational chaperones and nascent chain targeting/processing factors as they all vie for the limited surface area surrounding the nascent chain exit site 3 ? One body of work has shown that the ribosome-associated complex (RAC) facilitates Hsp70 activation and binding to specific nascent chain sites soon after they emerge from the exit tunnel [4][5][6][7] . The translating ribosome can also dynamically recruit the highly abundant nascent polypeptide-associated complex (NAC) to several distinct regions surrounding the exit site.…”
mentioning
confidence: 99%